2013
DOI: 10.2196/jmir.2738
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Caregiver Attitudes Toward Email Communication: Survey in an Urban Primary Care Setting

Abstract: BackgroundOverall usage of email communication between patients and physicians continues to increase, due in part to expanding the adoption of electronic health records and patient portals. Unequal access and acceptance of these technologies has the potential to exacerbate disparities in care. Little is known about the attitudes of pediatric caregivers with regard to their acceptance of email as a means to communicate with their health care providers.ObjectiveWe conducted a survey to assess pediatric caregiver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 16 publications
3
12
0
Order By: Relevance
“…However, it should be noted that in general educational and income levels as well as eHealth and health literacy levels were higher than usually found in the general Veteran population. This is consistent with existing literature suggesting that eHealth users tend to have higher levels of education, income, and eHealth and health literacy, than the general population (Archer et al, ; Cutrona et al, ; Dudas and Crocetti ; Kim and Nahm ). Perceptions of these two groups, sometimes shared, provide clear indications of changes needed to remove barriers and align expectations.…”
Section: Discussionsupporting
confidence: 91%
“…However, it should be noted that in general educational and income levels as well as eHealth and health literacy levels were higher than usually found in the general Veteran population. This is consistent with existing literature suggesting that eHealth users tend to have higher levels of education, income, and eHealth and health literacy, than the general population (Archer et al, ; Cutrona et al, ; Dudas and Crocetti ; Kim and Nahm ). Perceptions of these two groups, sometimes shared, provide clear indications of changes needed to remove barriers and align expectations.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings are consistent with a previously published research outside the VA, which found that older age was negatively associated with frequency of use to contact health care providers using email (ie, secure messaging) [ 16 ]. Consistent with previous findings, income was positively correlated with preferences to use email (ie, secure messaging) to communicate with health care providers [ 15 ]. Previous research has shown mixed findings about minority groups’ preferences for using email-type services to communicate with health care providers [ 15 , 16 ].…”
Section: Discussionsupporting
confidence: 88%
“…Consistent with previous findings, income was positively correlated with preferences to use email (ie, secure messaging) to communicate with health care providers [ 15 ]. Previous research has shown mixed findings about minority groups’ preferences for using email-type services to communicate with health care providers [ 15 , 16 ]. However, in our sample, minority status was consistent with findings that suggest a positive association between minority status and use of electronic email communication with health care providers [ 16 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The majority of studies were limited to parents or legal guardians (14/17, 82%); the remaining studies were of relatives as caregivers (3/17, 18%). The majority of participants were female, usually mothers [ 17 , 23 , 24 , 27 - 29 , 33 ]. A high proportion of racial and ethnic minorities were found in only 4 studies; African Americans were the largest group in these studies, with proportions ranging from 32% [ 21 ] to 83% [ 32 ].…”
Section: Resultsmentioning
confidence: 99%